ADVERTISING IN THE CONTEXT OF VIRTUALIZATION SOCIETY - Ороховська, Л. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article is an analysis of the impact of advertising means of mass media on the individual in order to form needs which really not required or new standards of living for the sake of profit producers of goods and services that transform the value- normative orientation of society.